1992
DOI: 10.1128/iai.60.8.3231-3237.1992
|View full text |Cite
|
Sign up to set email alerts
|

Differential morphologic and metabolic alterations in permissive versus nonpermissive murine macrophages infected with Legionella pneumophila

Abstract: Legionella pneumophila infection of macrophages from permissive guinea pigs and from AIJ mice compared with infection of cells from nonpermissive BDF, mice was studied by electron microscopy. The cells from the BDF1 mice were nonpermissive for legionella growth in vitro and showed few if any bacteria in phagosomes by electron microscopic examination. Similar electron micrographic examination of macrophages from A/J mice permissive for legionella growth showed numerous intact intracellular bacteria within 24 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…The cfu data and the MTT-viability results suggest that at 24 h postinfection, BALB/c macrophages probably express some unknown mechanism that makes them able to control the intracellular proliferation of L. pneumophila, while A/J macrophages are deficient in such a system. These data support our previous observation by electron microscopic examination whereby L. pneumophila were readily detected within A/J mouse TG macrophages after in vitro infection but were not seen within cells of other mouse strains [12].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The cfu data and the MTT-viability results suggest that at 24 h postinfection, BALB/c macrophages probably express some unknown mechanism that makes them able to control the intracellular proliferation of L. pneumophila, while A/J macrophages are deficient in such a system. These data support our previous observation by electron microscopic examination whereby L. pneumophila were readily detected within A/J mouse TG macrophages after in vitro infection but were not seen within cells of other mouse strains [12].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, nitric oxide metabolism might not be related to the genetic factors responsible for the differences in permissiveness between A/J and BALB/c macrophages. On the other hand, we previously reported that L. pneumophila vaccine is not capable of inducing detectable H202 and O 2 in macrophages [12], and that scavengers of HzO 2 (i.e. catalase) and O~ (superoxide dismutase) show little effect on the microbicidal activity of activated A/J macrophages to L. pneumophila [27].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Electron Microscopy. Macrophage monolayers on glass coverslips were prepared as previously described (9).…”
Section: Methodsmentioning
confidence: 99%